(3eMGSHI GdfaW h GdZGR (B/s - (3GdQGhj, YHO GdNGdb eWdcs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2011)
(3eONd Gdi UfGYI GdfaW h GdZGR h NUGFU eMGSHI GdfaW h GdZGR , GdfXGe GdeMGSHj h GdOdjd GdeMGSHj , eQGMd UfGYI GdfaW (B: (3eQMdI GdGSJWdGY h GdGSJcTGa , eQMdI GdMaQ h GdJWhjQ , eQMdI GfJGL h VN GdfaW h GdZGR , JhRjY JcGdja GdGfJGL GdeTJQcI Hjf GdfaW h GdZGR GdWHjYj , GdGUhd GdeJfGbUI h faGP GdeeJdcGJ GdefJLI , GfNaGV bjeI GdYbhO ZjQ GdeWhQI , GjQGO GdfaW GdNGe h GdZGR GdWHjYj , GdbhGFe GdeGdjI GdefMGSHjI , JcQjQ GdfaW , JSYjQ GdefJLGJ GdfaWjI , JcGdja fbd eTJbGJ GdfaW h GdZGR (B.s
(3eQGLY U(B.355s
Keywords: (3GdeMGSHIs; (3GdeMGSHI(B- (3GdfaWs; (3GdfaWs